Proceedings of the 4th International Conference on Security of Information and Networks 2011
DOI: 10.1145/2070425.2070453
|View full text |Cite
|
Sign up to set email alerts
|

Secure random number generation in wireless sensor networks

Abstract: Reliable random number generation is crucial for many available security algorithms, and some of the methods presented in literature proposed to generate them based on measurements collected from the physical environment, in order to ensure true randomness. However the effectiveness of such methods can be compromised if an attacker is able to gain access to the measurements thus inferring the generated random number. In our paper, we present an algorithm that guarantees security for the generation process, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…We mean by RBSs group, the group of RBSs that have the same length and are generated from ECG signals acquired from the same dataset for a specific duration. Equation (12) gives the minimum number of tests that must be passed for each NIST test [31]:…”
Section: C) Randomness Evaluation Based On Nist Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…We mean by RBSs group, the group of RBSs that have the same length and are generated from ECG signals acquired from the same dataset for a specific duration. Equation (12) gives the minimum number of tests that must be passed for each NIST test [31]:…”
Section: C) Randomness Evaluation Based On Nist Testsmentioning
confidence: 99%
“…Hence, they should be obtained from the output of an RNG [9]. In general, wireless sensor networks (WSNs) use PRNGs for generating random binary sequences (RBSs) [11], [12]. However, PRNGs require heavy computations to obtain randomness, and their seeds must be carefully chosen and protected, which in turn leads to the consumption of resources [11].…”
Section: Introductionmentioning
confidence: 99%
“…У праці [8] автори розробили та впровадили СГВЧ, криптографічний генератор псевдовипадкових чисел, який використовує отримані бітові помилки як джерело випадковості у вузлах бездротових датчиків. У праці [9] автори представили вдосконалену версію СГВЧ, запропоновану в праці [10], яка використовує вимірювання, отримані від бездротових вузлів датчиків, як джерела фізичної випадковості. Їх метод використовує розподілений алгоритм виборів лідерів для вибору випадкового джерела даних.…”
Section: постановка проблемиunclassified
“…In order to improve the original TRNG module, our recent proposal suggested that the task of providing source data for the random number generator was shared among multiple nodes, so as to hide the actual source of data from potential attackers. The random number generation process was made to depend on multiple sources via an authenticated readings collection (ARC) protocol, so that the attacker would be forced to tamper with a higher number of sensor boards before being able to gather a sufficient amount of information and break the TRNG.…”
Section: A Trng For Wireless Sensor Nodesmentioning
confidence: 99%